A Dynamic Partnership in New Frontiers – Africa - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, called the country "an exceptional example of an aid recipient turned donor" and urged business leaders to invest in Africa to help millions of Africans emerge from poverty, while also finding strong economic returns in new markets. It used to be that if you wanted to do something around development, the focus was on official development assistance, foreign aid. Korea is one of the countries that benefited tremendously from foreign assistance. The World Bank made many investments in the Republic of Korea and to a great extent some of the greatest successes were related to the relationship between the Republic of Korea and the World Bank Group. For countries to have the same experience that Korea has had--going from one of the poorest countries in the world to now being the 14th largest economy in the world--the private sector will have to play a critically important role.